The Role Of Artificial Intelligence In Early Detection Of Breast Cancer (The Review of Diabetic Studies, 2025)
Introduction: Early cancer diagnosis increases the likelihood of implementing an effective treatment in many tumor groups. Out of all cancer types, breast cancer is currently the most prevalent kind that affects women globally. Genetics, lifestyle, and environmental factors are among the many factors that have led to the increase in the prevalence of breast cancer among women from all socioeconomic backgrounds. As a result, appropriate screening for prompt diagnosis and treatment becomes crucial to the fight against the condition. Early breast cancer diagnosis could be revolutionized with the help of Artificial intelligence (AI) machine learning, which trains computers to recognize complex patterns in data and make predictions.Aim of the Study: The purpose of the present review is to understand the role of Artificial intelligence (AI) in early diagnosis of breast cancer.Methodology: The review is a comprehensive research of PUBMED since the year 2005-2022. Conclusion: Artificial intelligence (AI) is revolutionizing many aspects of our lives with its many applications. Results are even more easily and conveniently obtained when AI is used in the current screening process for breast cancer. Important strategies involve identifying patients who are at risk but do not exhibit symptoms, and promptly and suitably examining those who do. Among the advantages of using AI techniques for breast cancer screening are faster and more precise results. However, there are numerous obstacles in the way of AI integration that must be methodically overcome.